Probing the Schrödinger-Newton equation in a Stern-Gerlach-like experiment - Aguiar, Gabriel H. S. [UNESP]; Matsas, George E. A. [UNESP] (Amer Physical Soc, 2024)
Explaining the behavior of macroscopic objects from the point of view of the quantum paradigm has challenged the scientific community for the past century. A mechanism of gravitational self-interaction, governed by the so-called Schrodinger-Newton equation, is among the proposals that aim to shed some light on it. Despite all efforts, this mechanism has been proven difficult to probe. Here, we consider a Stern-Gerlach-like experiment to try it out. The Schrodinger-Newton equation can be analytically solved under certain proper conditions, and a change-of-phase effect induced by the gravitational self-interacting potential can be calculated.